Corn Tiller Yield Contributions and Ear Development in Low Plant Densities - R. Veenstra; C. D. Messina; D. Berning; S. Wallace; M. Legleiter; L. Haag; P. V. Prasad; I. A. Ciampitti (Kansas Agricultural Experiment Station Research Reports, 2021)
Research in modern corn (Zea maysL.) hybrids investigating tiller contributions and ear development at low plant densities is scarce, particularly in water-limited environments. To fill this research gap, a second season of replicated experiments was conducted in 2020 at 7 sites across Kansas (Keats, Buhler, Greensburg, Garden City, Goodland, and two sites in Colby) evaluating two common, tiller-prone corn hybrids (P0805AM and P0657AM) at three target plant density levels (10000, 17000, and 24000 plants/a). Five of the listed sites also considered a tillering factor (tiller removal at development stage V10 [tenth-leaf] or tiller maintenance). Seasonal phenology, partitioned grain yield, harvested ear type characterizations, and environmental conditions were recorded and analyzed to quantify tiller contributions in each site. Results showed that intact tillers had either no effect or were able to boost yields. In the best environments, tillers were able to successfully compensate for losses of 60% in plant density. Five of the seven tested sites produced approximately 50% of total harvested ears as desirable tiller lateral ears in the 10000 plants/a target plant density. The highest percentage of undesirable tiller tassel ear development in the 10000 plants/a density was 13%. Future research will seek to find explanations of the ear type relationships on a deeper level and predict tiller yield contributions considering various environments and ear development outcomes.
Keywords: corn; tillers; plant density; yield; ear development